Microarrays - Müller, Hans-Joachim (Elsevier Academic Press, 2006)
Microarray technology allows us to answer many questions about gene expression and drug-target screening by employing high-throughput screening. This book dedicates itself to microarrays with clear and understandable explanations and an overview of the presently available hardware, biochips and software. Separate chapters cover the different requirements for DNA and protein chips as well as spotters and scanners.